Artemisia argyi essential oil modulates lipid metabolism via linoleic acid and glycerophospholipid pathways in high-fat diet-induced obese mice - Wang, Kaijun; Yang, Anqi; Li, Yunxia; Han, Qi; Yin, Zhangzheng; Xia, Siting; Chen, Jiayi; Mo, Jiahao; Bin, Peng (Frontiers in Nutrition, 2025)
Obesity is a nutritional disorder caused by an imbalance between energy intake and expenditure. The natural products will provide hypolipidemic active factors that will intervene in obesity and its complications, as well as direct drug treatment. Artemisia argyi leaf is a well-known species in traditional Chinese medicine, and its essential oil (AAEO) has been identified to exert various physiological activities. This study investigates the chemical composition of essential oil extracted from Artemisia argyi (AAEO) and its potential effects on intestinal microbial function and lipid metabolism in mice subjected to a high-fat diet (HFD). The essential oil was extracted and analyzed for its bioactive compounds, revealing a rich presence of terpenes and oxygenated derivatives. Utilizing LC-MS/MS technology combined with multivariate statistical methods, significant alterations in serum metabolites were observed in AAEO-treated mice compared to those on HFD alone. Key metabolic pathways impacted by AAEO included linoleic acid metabolism and glycerophospholipid metabolism. These findings suggest that while AAEO did not significantly alter gut microbiota composition, it substantially modulated lipid metabolism via linoleic acid and glycerophospholipid pathways, suggesting a potential natural strategy for obesity-related metabolic disorders. This study provides new insights into the application of Artemisia argyi essential oil in dietary interventions and obesity management.